Constructive in the ESL writing classroom: A case for collaborative essay writing / Noor Hanim Rahmat - Rahmat, Noor Hanim (Academy of Language Studies, 2014)
This paper reports a case study on how movies and collaborative writing influence ESL writing classroom.